Vitamin intake and pancreatic cancer risk reduction: A meta-analysis of observational studies - Liu, Ying (Medicine (Baltimore), 2018)
BACKGROUND: The relationship between vitamin intake and pancreatic cancer (PC) risk is disputed. We aimed to investigate the association between vitamin intake and the risk of PC via meta-analysis. METHODS: We conducted a meta-analysis of studies concerning vitamin intake and the risk of PC from EMBASE, MEDLINE, and Cochrane Library. The search yielded 25 correlative studies including 1,214,995 individuals. The relative risks (RR) were examined by a random-effect model or fixed-effect model. Subgroup analysis, dose–response analysis, sensitivity analysis, meta-regression, and publication bias analysis were used to analyze studies. RESULTS: The RR of PC in the highest vitamin intake group was 0.90 (95% confidence interval, 0.83–0.98) compared with that in the lowest vitamin intake in the prospective studies. Different increments of vitamin intake and the risk of PC were examined with dose–response analysis, and a decrease in the risk of PC was observed with vitamin D (25%) and vitamin B12 (27%). CONCLUSIONS: This meta-analysis found that vitamin intake can decrease the risk of PC, particularly vitamin D and vitamin B12.